Determinación cuantitativa de residuos de fluoroquinolonas en la carne de pollo comercializada en el cantón Machala provincia de El Oro - Mendía Polo, Estefanía Giselle (2017)
Antibiotics are chemicals produced by microorganisms that kill or prevent the reproduction of certain kinds of bacteria. In poultry farming are generally used for prophylactic purposes, therapeutics and animal growth promoters. Fluoroquinolones, are a group of broad-spectrum antibiotics mainly used in production for the treatment of infections in the respiratory tract and urinary tract of birds, their misuse causes the accumulation of residues in the meat of the animal generating a high Risk to human health. The Ecuadorian population consumes about 230 million chickens a year, therefore, it is of the utmost importance that the meat of the chicken is harmless. The present study aimed at the quantitative determination of fluoroquinolone residues (Enrofloxacin, Ciprofloxacin, Danofloxacin, Norfloxacin, pipemidic acid, ofloxacin, flumequine, oxolinic acid, cinoxacin) in chicken meat marketed in the city of Machala using a rapid test (MaxSignal Floroquinolone ELISA test Kit), which consists of a competitive colorimetric Elisa assay that determines the quantitative presence of fluoroquinolines in chicken meat. In this study, a total of 46 samples of chicken meat (breast) were taken, which are marketed in markets and grocery stores in the city of Machala, dividing the sampling in urban areas (Mercado Central, Mercado 25 de Junio and Mercado Sur) and peripheral zone (Mercado Puerto Bolívar, Mercado Buenos Aires and grocery stores) from the city. The results determined that of the 46 chicken samples, 22 were positive to fluoroquinolones representing 47.57% of the total and 24 were negative representing 52.17%. The concentrations of antibiotics in the positive samples were presented with a minimum of 0.002 ng / g and a maximum of 0.607 ng / g, the average concentration of fluorouinolones found was 0.157 ng / g. Of the 22 positive cases of the test, 65.60% correspond to the outlets in the urban center, and of the 24 negative cases of the test, 92.9% correspond to the outlets in the peripheral sector from the city. A survey was applied to the drug sales centers and it was determined that the most commercialized antibiotic in the poultry industry is fluoroquinolone with 23,02%, followed by tetracyclines with 22,62%. In the statistical analysis with the chi-square test applied, there was a significant statistical association between the variable presence of fluoroquinolones and the origin of the samples with a p-value of 0.000239 (p <0.05). This study showed that poultry meat commercialized in the city showed residues of fluoroquinolones at 47.5%; however, the antibiotic concentrations found were below the maximum residue limits (MRLs) set by Codex Alimentarius and the European Union (EU), demonstrating compliance with the withdrawal time indicated for this product. It is recommended that the use of drugs for the breeding of birds be prescribed by a specialist, respecting the time of withdrawal before slaughter, and also schedule training by state institutions for producers and consumers about the consequences of eating meat with residues of antibiotics.